Design of Mathematics Teaching Materials Based on Local Wisdom for Strengthening Mathematical Literacy on Social Arithmetic Material - Prabawati, Mega Nur; Santika, Satya; Mulyani, Eva (Department of Mathematics Education Program IPI Garut, 2024)
Abstrak Penelitian ini bertujuan untuk mengidentifikasi profil awal kemampuan literasi matematis siswa, merancang dan mengembangkan bahan ajar matematika berbasis kearifan lokal untuk meningkatkan literasi matematis, dan mendeskripsikan hasil belajar siswa setelah menggunakan bahan ajar tersebut. Penelitian ini menggunakan pendekatan Research and Development (R&D) dengan menggunakan model ADDIE, yang meliputi lima tahap yaitu analisis, desain, pengembangan, implementasi, dan evaluasi. Pada tahap analisis, tingkat literasi matematika siswa kelas 9 di empat sekolah menengah pertama (SMPN 1 & 2 Sukahening, SMPN 6 & 14 Tasikmalaya) ditemukan pada level 2-3, berdasarkan kerangka kerja PISA. Pada tahap desain, dibuatlah rencana pembelajaran yang mengintegrasikan unsur-unsur kearifan lokal Tasikmalaya. Pada tahap pengembangan, handout interaktif dibuat dengan menggunakan Canva, dengan menggabungkan pilihan font, warna, dan grafik tematik. Soal pre-test/post-test dan kuesioner persepsi siswa juga dikembangkan dan divalidasi oleh ahli materi dan ahli media, yang menghasilkan nilai kelayakan sebesar 92% (sangat layak). Siswa menyelesaikan pre-test sebelum menggunakan handout dan post-test setelahnya, diikuti dengan kuesioner tentang kepraktisan dan persepsi. Analisis data menunjukkan peningkatan rata-rata penguasaan pembelajaran dari 50,84% (pre-test) menjadi 71,18% (post-test). Siswa memberikan tanggapan yang sangat positif mengenai isi, desain, dan relevansi budaya dari materi. Abstract This study aims to identify students' initial profiles of mathematical literacy skills, design and develop mathematics teaching materials based on local wisdom to enhance mathematical literacy, and describe students’ learning outcomes after using these materials. The research employs a Research and Development (R&D) approach using the ADDIE model, which includes five phases: analysis, design, development, implementation, and evaluation. In the analysis phase, the mathematical literacy level of 9th-grade students at four junior high schools (SMPN 1 & 2 Sukahening, SMPN 6 & 14 Tasikmalaya) was found to be at levels 2–3, based on the PISA framework. During the design phase, lesson plans were created that integrated elements of Tasikmalaya’s local wisdom. In the development phase, interactive handouts were created using Canva, incorporating thoughtful choices of fonts, colors, and thematic graphics. Pre-test/post-test questions and student perception questionnaires were also developed and validated by a content expert and a media expert, resulting in a feasibility score of 92% (highly feasible).The implementation took place over four class sessions across the selected schools. Students completed a pre-test before using the handouts and a post-test afterward, followed by a questionnaire on practicality and perception. Data analysis showed an increase in average learning mastery from 50.84% (pre-test) to 71.18% (post-test). Students gave highly positive responses regarding the content, design, and cultural relevance of the materials.